Inequality in Mortality between Black and White Americans by Age, Place, and Cause, and in Comparison to Europe, 1990-2018 - Hannes Schwandt; Janet Currie; Marlies Bär; James Banks; Paola Bertoli; Aline Bütikofer; Sarah Cattan; Beatrice Zong-Ying Chao; Claudia Costa; Libertad Gonzalez; Veronica Grembi; Kristiina Huttunen; et al. (Institute of Labor Economics (IZA), 2021)
Although there is a large gap between Black and White American life expectancies, the gap fell 48.9% between 1990-2018, mainly due to mortality declines among Black Americans. We examine age-specific mortality trends and racial gaps in life expectancy in rich and poor U.S. areas and with reference to six European countries. Inequalities in life expectancy are starker in the U.S. than in Europe. In 1990 White Americans and Europeans in rich areas had similar overall life expectancy, while life expectancy for White Americans in poor areas was lower. But since then even rich White Americans have lost ground relative to Europeans. Meanwhile, the gap in life expectancy between Black Americans and Europeans decreased by 8.3%. Black life expectancy increased more than White life expectancy in all U.S. areas, but improvements in poorer areas had the greatest impact on the racial life expectancy gap. The causes that contributed the most to Black mortality reductions included: Cancer, homicide, HIV, and causes originating in the fetal or infant period. Life expectancy for both Black and White Americans plateaued or slightly declined after 2012, but this stalling was most evident among Black Americans even prior to the COVID-19 pandemic. If improvements had continued at the 1990-2012 rate, the racial gap in life expectancy would have closed by 2036. European life expectancy also stalled after 2014. Still, the comparison with Europe suggests that mortality rates of both Black and White Americans could fall much further across all ages and in both rich and poor areas. Significance Statement From 1990-2018, the Black-White life expectancy gap fell 48.9% though progress stalled after 2012 as life expectancy plateaued or declined. If improvements had continued at the 1990-2012 rate, the racial gap in life expectancy would have closed by 2036. Black life expectancy in 1990 started below European or White American levels but grew at a faster rate: the gap between Europeans and Black Americans decreased by 8.3% between 1990-2018. In 1990 White Americans and Europeans in rich areas had similar life expectancy, while White Americans in poor areas had lower life expectancy than poor Europeans. But all White Americans have lost ground relative to Europeans. Current incomebased life expectancy gaps are starker in the U.S. than in comparable European countries.
Keywords: I14; 330; life expectancy; racial disparity; area-level socioeconomic status; international comparison